Intergenerational mobility in socio-emotional skills - Orazio P. Attanasio; Áureo de Paula; Alessandro Toppeta (The Institute for Fiscal Studies (IFS), 2024)
This paper investigates the intergenerational transmission of socio-emotional skills during childhood, using data from the 1970 British Cohort Study (BCS70) in the United Kingdom. This dataset enables us to measure two dimensions of socio-emotional development: internalising and externalising skills. More importantly, we can use multiple measures of parents' skills collected during both their childhood and their adulthood. Whereas parent-child skills are strongly related when both are measured contemporaneously, they remain correlated when both are measured in childhood, with a stronger transmission observed from mothers to their children. Additionally, by leveraging the BCS70 data on socio-emotional skills for three generations, we estimate multi-generational persistence. Notably, we find a correlation between the grandmother's internalising skill and the grandchildren's skills, even after accounting for parental skills.
Keywords: J62; D63; I21; J24; 330; Intergenerational Mobility; Inequality; Socio-emotional Skills; Spectral gap mobility index